Review of procaryote metabolism in view of modeling microbial adaptation from fast growth to starvation conditions. Issue 6 (1st November 2005) - Lavallée, B; Lessard, P; Vanrolleghem, P A
Abstract : More than 50 years ago, Monod (1949) proposed the application of the Michaelis–Menten relation describing enzyme kinetics to a culture of microorganisms. For the purpose of simplification, the mathematical relation proposed by Monod (1949) reduced the entire cell to a single enzyme genetically expressed in a single intensity. However, cell metabolism is based on a large number of biochemical reactions. This paper reviews the literature to identify the controlling factors of cell metabolism and the regulation of specific activity of the cell. The literature review was designed to highlight which regulation mechanisms induce a growth-rate variation so that they can be expressed mathematically. The study of these processes will focus on modeling the specific activity variation. The review is limited to heterotrophic procaryote organisms under aerobic conditions. Key words : modeling, metabolism, regulation, growth rate, cell death, maintenance, activated sludge.